Glucocorticosteroids - a new target in the treatment of metabolic syndrome - Szymon Baumgart; Daria Kupczyk; Renata Studzińska (Polish Pharmaceutical Society, 2024)
Glucocorticoids are hormones belonging to the group of steroid hormones produced by the adrenal cortex and are necessary for the proper maintenance of metabolic (including lipid and carbohydrate metabolism) and homeostatic functions of the human body. Glucocorticoid secretion is regulated peripherally by the hypothalamic-pituitary-adrenal (HPA) axis in a double feedback fashion, but also at the tissue level by 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) and type 2 (11β-HSD2). 11β- hydroxysteroid dehydrogenase type 1 is an enzyme that catalyzes the intracellular conversion of biologically inactive cortisone into biologically active cortisol, while 11β- hydroxysteroid dehydrogenase type 2 catalyzes the reverse reaction. Excess glucocorticoids disrupt the body's metabolic management, which leads to the development of metabolic disorders such as abdominal obesity, insulin resistance, or dyslipidemia. In recent years, it has been proven that impaired regulation of the activity of 11β-hydroxysteroid dehydrogenase type 1, especially that located in visceral adipose tissue, is the pathogenetic basis of diseases such as obesity or type 2 diabetes, which are related and constitute important components of the metabolic syndrome. Therefore, inhibition of 11β-HSD1 is a promising concept for the therapy of diseases associated with the metabolic syndrome. Therefore, over the last three decades, there has been significant activity in the academic and pharmaceutical communities towards exploring the role of this enzyme in the pathogenesis of the metabolic syndrome and discovering new chemical compounds as specific 11β-HSD1 inhibitors. The aim of the following study was to present the role of glucocorticosteroids and 11β-hydroxysteroid dehydrogenase type 1 in the pathogenesis of the metabolic syndrome and the importance of using 11β-HSD1 inhibitors in the therapy of this disease. In addition, the work reviews the most important 11β-HSD1 inhibitors and compounds currently being tested for the inhibition of this enzyme.